2013
DOI: 10.1309/ajcpo64iwnlycvvb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the International Society on Thrombosis and Haemostasis and Institutional Diagnostic Criteria of Disseminated Intravascular Coagulation in Pediatric Patients

Abstract: Globally, adult intensive care units routinely use the International Society on Thrombosis and Haemostasis (ISTH) scoring system for identifying overt disseminated intravascular coagulation (DIC). However, in our pediatric intensive care unit, a modified diagnostic criterion (Texas Children’s Hospital [TCH] criteria) that requires serial monitoring of the coagulation variables is employed. A retrospective analysis of 2,136 DIC panels from 130 patients who had at least 4 DIC panels during 1 admission to a pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 13 publications
1
41
0
2
Order By: Relevance
“…Not a few studies of DIC caused mainly by infections have concluded that fibrinogen should be excluded from DIC scoring systems [15,16,17]. In those studies of mainly infection-related DIC, decreases in fibrinogen were rare, primarily because fibrinogen is an acute-phase protein and its plasma level increases during the acute-phase response, especially in inflammatory conditions [15,17]. In contrast, in hematological malignancy-related DIC patients, hypofibrinogenemia is not rare.…”
Section: Discussionmentioning
confidence: 99%
“…Not a few studies of DIC caused mainly by infections have concluded that fibrinogen should be excluded from DIC scoring systems [15,16,17]. In those studies of mainly infection-related DIC, decreases in fibrinogen were rare, primarily because fibrinogen is an acute-phase protein and its plasma level increases during the acute-phase response, especially in inflammatory conditions [15,17]. In contrast, in hematological malignancy-related DIC patients, hypofibrinogenemia is not rare.…”
Section: Discussionmentioning
confidence: 99%
“…DIC is a clinico-laboratory diagnosis 4. The diagnosis is considered only in patients with an underlying disorder, which is known to be associated with DIC in conjunction with several laboratory features.…”
Section: Diagnosis Of Dicmentioning
confidence: 99%
“…2 The criteria have 91% sensitivity with 97% specificity among adults and demonstrated strong correlation between DIC score with incidence of mortality 18. Unfortunately, data on validation of ISTH DIC criteria in children are limited, even though it has been used universally in paediatric patients 4. Furthermore, to our knowledge no studies have evaluated the sensitivity and specificity of ISTH DIC criteria in neonates.…”
Section: Diagnosis Of Dicmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiyolojide sepsis, vaskülit, hipoksi, travma, uygunsuz kan transfüzyonları, dev hemanjiomlar ve başlıca akut promiyelositik lösemi olmak üzere maligniteler yer alır (4)(5)(6). Endotelyal hasar ve mikrovasküler tromboza zemin hazırlayan nedenler arasında artmış serbest oksijen radikallerinin varlığı ve lipid peroksidasyonu sonucu oluşan endotel disfonksiyonu sorumlu tutulmaktadır (7). Reaktif oksijen türlerine karşı enzimatik korumayı sağlayan, protein oksidasyonu ve DNA'daki hasarı önleyen süperoksit dismutaz, katalaz, glutatyon peroksidaz, glutatyon redüktaz gibi çeşitli enzim sistemleri vardır.…”
Section: Introductionunclassified